(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The economic security of the banking sector, driven by its sustainable development, serves as a fundamental pillar of a country’s overall economic security. This paper is dedicated to the issues of ensuring the economic security of commercial banks in conditions of instability and uncertainty. The main focus is on the role of risk management systems as a key tool for minimizing potential threats and losses faced by banks. The relationship between key factors of financial stability, such as capital adequacy, liquidity, asset quality, and liability structuring, is examined. The importance of thorough diagnostics and objective economic justification for each of these criteria in maintaining stability and protecting the bank from potential risks is emphasized. The paper also highlights the need for a comprehensive approach in organizing the economic security system, which includes not only traditional financial measures but also effective risk management.